Nearpod as a Digital Learning Tool: Its Effect on Mathematical Critical Thinking Skills in Vocational High School - Windia Hadi; Sri Mariana; Widyah Noviana; Fatimah az Zahra; Fanuel Alem Semere (FKIP Universitas Lampung, 2026)
Technology has become an important tool to assist student learning in the 21st century. Nearpod is an interactive digital learning platform that allows teachers to create, share, and manage learning materials with interactive features. In fact, critical thinking skills are still very low among vocational secondary school students. The purpose of this study is to determine whether the Nearpod intervention has a significant effect on critical thinking skills in both the experimental and control classes, and to assess the magnitude of this effect specifically in the experimental class. This study used an experimental method with a non-equivalent posttest design, involving 68 eleventh-grade students as samples. Purposive sampling was used as the sampling technique. There were two groups: the experimental group used Nearpod, while the control group used conventional learning, which is what teachers usually do without Nearpod. The instrument used in this study was a critical thinking test consisting of five valid and reliable essay questions. This study was analyzed using a normality test, a homogeneity test, a two-sample t-test, and Cohen's d to determine the magnitude of the effect. The results of this study show that Nearpod use influences students' critical thinking skills compared with students who do not use Nearpod, with an effect size (d = 0.50) classified as a moderate, significant positive effect. Thus, Nearpod has a positive impact on the critical thinking skills of vocational high school students. Nearpod can help students develop their critical thinking skills and serve as an alternative digital learning tool for teachers to use in the classroom. Keywords: mathematical critical thinking, nearpod, interactive learning, vocational high school students.